Analysis of the Similiarity Level of Source Code in the Kotlin Programming Language using Winnowing Algorithm - Astica, Yustikamasy; Utami, Ema; Hartanto, Anggit Dwi (Universitas Dharma Wacana, 2023)
Plagiarism is an act of imitating the work of others directly or indirectly. In an academic environment, plagiarism applies not only to textual documents but also to source code documents. Source code plagiarism in academia usually occurs when students copy another student's code and submit it as if it were the student's work. So that an automatic plagiarism check is needed, the winnowing algorithm will be used to help detect similarities in source code as a way to detect an act of plagiarism. The Winnowing algorithm, which is usually used to detect document plagiarism, this research detects the source code. The results produced in this study are that the degree of similarity in the two source codes will produce different similarity values if the dataset used has gone through the text preprocessing stage or without preprocessing. If the dataset has gone through the text preprocessing stage, the similarity value will be pretty low because the number of characters used is significantly reduced. The Winnowing and Jaccard Similarity algorithms quickly detect plagiarism in source code and can be used to minimize plagiarism.